Prevailing PA mutation K356R in avian influenza H9N2 virus increases mammalian replication and pathogenicity - Xu, Guanlong; Zhang, Xuxiao; Gao, Weihua; Wang, Chenxi; Wang, Jinliang; Sun, Honglei; Sun, Yipeng; Guo, Lu; Zhang, Rui; Chang, Kin-Chow; Liu, Jinhua; Pu, Juan (American Society for Microbiology, 2016)
Adaptation of the viral polymerase complex comprising PB1, PB2, and PA is necessary for efficient influenza A virus replication in new host species. We found that PA mutation K356R (PA-K356R) has become predominant since 2014 in avian H9N2 viruses in China as with seasonal human H1N1 viruses. The same mutation is also found in most human isolates of emergent avian H7N9 and H10N8 viruses whose six internal gene segments are derived from the H9N2 virus. We further demonstrated the mammalian adaptive functionality of the PA-K356R mutation. Avian H9N2 virus with the PA-K356R mutation in human A549 cells showed increased nuclear accumulation of PA and increased viral polymerase activity that resulted in elevated levels of viral transcription and virus output. The same mutant virus in mice also enhanced virus replication and caused lethal infection. In addition, combined mutation of PA-K356R and PB2-E627K, a well-known mammalian adaptive marker, in the H9N2 virus showed further cooperative increases in virus production and severity of infection in vitro and in vivo. In summary, PA-K356R behaves as a novel mammalian tropism mutation, which, along with other mutations such as PB2-E627K, might render avian H9N2 viruses adapted for human infection.